1986
DOI: 10.1210/jcem-62-4-723
|View full text |Cite
|
Sign up to set email alerts
|

Class II Major Histocompatibility Complex Antigen Expression and Cellular Interactions in Thyroid Glands of Graves' Disease

Abstract: Class II major histocompatibility complex (MHC) antigens have been demonstrated on the surface of thyroid epithelial cells (thyrocytes) from patients with autoimmune thyroid disease. The present study was designed to investigate how the expression of class II MHC antigens is involved in autoimmune processes in Graves' disease by studying cellular interactions among thyrocytes, lymphocytes within thyroid glands (TG), and peripheral blood (PB) lymphocytes. Thyrocytes were prepared by collagenase digestion, and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

1987
1987
2001
2001

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(29 citation statements)
references
References 20 publications
3
26
0
Order By: Relevance
“…We also observed that the concentration of FCS did not influence the levels of sICAM-1 which were identical with 10% FCS or 10% NU-serum, a synthetic product containing only 1% serum. These results corroborate those of Ciampolillo et al (1993) who tested only membrane ICAM-1 culture Several reports have been published on human thyrocytes cocultured in monolayers with autologous PBL or ITL lymphocytes (Davies et al 1985, Iwatani et al 1986, Matsunaga et al 1986, Otsubo et al 1988, Sato et al 1993, Massart et al 1995, 1996. However, our present work is the first demonstration of the action of PBL and ITL cocultured with autologous thyrocytes on the expression of membrane and soluble ICAM-1.…”
Section: Discussionsupporting
confidence: 90%
“…We also observed that the concentration of FCS did not influence the levels of sICAM-1 which were identical with 10% FCS or 10% NU-serum, a synthetic product containing only 1% serum. These results corroborate those of Ciampolillo et al (1993) who tested only membrane ICAM-1 culture Several reports have been published on human thyrocytes cocultured in monolayers with autologous PBL or ITL lymphocytes (Davies et al 1985, Iwatani et al 1986, Matsunaga et al 1986, Otsubo et al 1988, Sato et al 1993, Massart et al 1995, 1996. However, our present work is the first demonstration of the action of PBL and ITL cocultured with autologous thyrocytes on the expression of membrane and soluble ICAM-1.…”
Section: Discussionsupporting
confidence: 90%
“…TFC from autoimmune thyroid diseased glands have been shown to be capable of presenting autoantigens lo self-reactive lymphocytes and to enhance the activation of autologous lymphocytes [24][25][26]. Additionally, it has been demonstrated that susceptibility to killing by cytotoxic T cells is dependent on the level of MHC class I expression by the target cell [27].…”
Section: Discussionmentioning
confidence: 99%
“…For IL-1 treatment in the Western blot analyses, each cell line was treated with recombinant human IL-1 (10 ng/ml) for 48 h without FCS for NIM1 cells and with 10% FCS for NPA cells. The methods of preparing thyrocytes from patients with Graves' disease, which we used as a negative control in Western blot analyses, are described in detail elsewhere (Matsunaga et al 1986). …”
Section: Cell Culturementioning
confidence: 99%